Factors associated with time free of oral candidiasis in children living with HIV/AIDS, São Paulo, Brazil - Thais Claudia Roma de Oliveira Konstantyner; Aline Medeiros da Silva; Luana Fiengo Tanaka; Heloísa Helena de Sousa Marques; Maria do Rosário Dias de Oliveira Latorre (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2013)
In clinical practice, recurrence of thrush is common in children living with HIV/AIDS. The aim of this study was to determine the factors associated with time spent free of oral candidiasis using survival analysis for recurrent events. A retrospective cohort study was carried out with 287 children treated between 1985 and 2009 at a reference center in the city of São Paulo, Brazil. The Prentice, Williams and Peterson model for recurrent events was used for the investigation of factors associated with the time free of oral candidiasis. The following factors were associated with the time patients were free of oral candidiasis: moderate immunodepression (HR = 2.5; p = 0.005), severe immunodepression (HR = 3.5; p < 0.001), anemia (HR = 3.3; p < 0.001), malnutrition (HR = 2.6; p = 0.004), hospitalization (HR = 2.2; p < 0.001), monotherapy (HR = 0.5; p = 0.006), dual therapy (HR = 0.3; p < 0.001) and triple therapy/highly active antiretroviral therapy (HR = 0.1; p < 0.001). The method analyzed in the present study proved useful for the investigation of recurrent events in patients living with HIV/AIDS.